Two-phase thermosyphon for boiling characterisation of micro/nanostructured metal additively manufactured materials - Soh, Yong Kien (Nanyang Technological University, 2023)
In the contemporary era, with the rapid advancements of modern electronic technology, the size of components, including microchips, are progressively shrinking. Despite the benefits of the miniaturization of microchips, the heat generation rate remains constant or higher, which leads to the problem of overheating in numerous devices. Consequently, efficient heat dissipation is critical to minimize thermal hotspots in electronic chips to ensure their reliability and efficiency. In this regard, researchers are currently exploring pool boiling cooling method, which is widely acknowledged as one of the most effective heat transfer techniques in the thermal industry. This study aims to develop a functional two-phase thermosyphon to characterise the pool boiling performances of an additively manufactured material for future studies of micro/nanostructured metal. To fulfill the requirement of developing a thermosyphon setup for water pool boiling without the usage of a condenser, it is necessary to calculate the heat losses through the entire setup and the rate of water level drop through evaporation and vaporization. Following the calculation of heat losses and water level drop rate, multiple three-dimensional models of the thermosyphon were developed using Solidworks software. Subsequently, computational fluid dynamics (CFD) simulation was performed using the “Ansys” software to evaluate its effectiveness of each design in achieving the desired outcome. Upon completing the simulation, a three-dimensional model for the entire thermosyphon system was developed from which elaborate two-dimensional engineering drawings were produced for every individual component, which was then used for manufacturing. A study was done to validate the boiling setup and explore the influence of surface roughness on boiling performance. Plotting the heat flux against the heat transfer coefficient and the heat flux against the temperature of the wall superheat after evaluating the experimental data revealed that a 32% increase in the critical heat flux value occurred when the surface roughness value increases from 0.043µm to 1.839 µm. In order to investigate the impact of surface roughness on bubble departure time, the experiment also included high-speed bubble visualisation. Another study was conducted on boiling degeneration in a range of additive manufacturing (AM) samples with varying etch durations and heat treatment temperatures, all of which were boiled in HFE7100. It was observed that most of the samples exhibited degradation after just one second of boiling. To investigate the cause of this degradation, the sample which demonstrated the more significant degeneration were further investigated by boiling it in ethanol and it was determine that the fluid played a role to the degeneration process.